2004
DOI: 10.1002/app.21136
|View full text |Cite
|
Sign up to set email alerts
|

Water‐swellable hydrophobic porous copolymer resins based on divinylbenzene and acrylonitrile. I. Water‐swelling behavior

Abstract: Hydrophobic porous copolymer resins based on divinylbenzene (DVB) and acrylonitrile (AN) could be prepared as directly swellable in water by using purified DVB (98.8%) and technical DVB (79.3%) in the presence of 1,2-dichloroethane as porogen. Compared with the resins based on DVB and methyl acrylate (MA/DVB resins), the AN/DVB resins thus obtained are waterswellable over a wider range of copolymer compositions, and the swelling ability of the AN/DVB resins in water was further confirmed by investigating the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In a previous paper we have shown that by copolymerization of purified DVB and AN with DCE as porogen, the resulting AN/DVB resins with DVB contents up to 60% (79% by weight) are water wettable or swellable 1. In Figure 1, the specific surface areas for the 40, 50, and 60% DVB resins are 575, 632, and 704 m 2 /g, with a porosity (pore volume) of 62.9% (1.38 mL/g), 59.2% (1.23 mL/g), and 55.6% (1.08 mL/g), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous paper we have shown that by copolymerization of purified DVB and AN with DCE as porogen, the resulting AN/DVB resins with DVB contents up to 60% (79% by weight) are water wettable or swellable 1. In Figure 1, the specific surface areas for the 40, 50, and 60% DVB resins are 575, 632, and 704 m 2 /g, with a porosity (pore volume) of 62.9% (1.38 mL/g), 59.2% (1.23 mL/g), and 55.6% (1.08 mL/g), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Copolymer resins were prepared, as described in the previous paper,1 by using purified DVB (98.8%) or technical DVB (79.3%), through a usual suspension copolymerization method 8, 9. For all resin samples the contents of DVB and AN in the starting reaction mixture are expressed as a mole percentage of the total amount of monomers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 The swellability of HCPs can be affected by a number of parameters including the initial monomer concentration, 21 the extent of monomer crosslinking and the solvating state of the growing polymer chains (nature of reaction solvent). 31,32 The polarity of the polymer can also influence the swellability of the polymers. For instance, a HCP prepared via self-condensation using FeCl 3 demonstrated the liquid phase adsorption of hydroxymethylfurfural (HMF).…”
Section: Introductionmentioning
confidence: 99%